Evoluzione storica della farmacoutilizzazione degli anti-ipertensivi in Italia (1988-1998) - Bologna, Enrico; Russo, Pierluigi; Licata, Sabrina; Civalleri, Liliana; Caprino, Luciano (Farmeconomia. Health economics and therapeutic pathways, 2003)
The aim of this study was to perform an historical evaluation of pharmacoutilization of main antihypertensive drug classes in Italy between 1988 and 1998. There were analysed numbers of packs and costs for diuretics, beta-blockers, central and peripheral antihypertensive drugs (CPAD), calcium-channel blockers (CCB), angiotensin-converting enzyme (ACE) inhibitors and angiotensin-II (AII) receptor antagonists. The amount of defined-daily-doses (DDDs) per preparation was calculated by dividing the annual number of packs by respective DDD value. The number of DDDs was grouped according to the second level of the anatomic-therapeutic-chemical (ATC) classification. The amount of annual expenditures for each ATC level was converted to current monetary values. To calculate the annual cost per DDD, the expenditure was divided by respective number of DDDs. From 1988 to 1998, total number of DDDs of antihypertensive drugs grew from 193.657.092 to 396.140.967 with an increase of 105%, while the expenditure grew from 40.886.385 to 126.102.362, with an increase of 208%. Comparing data of 1990 and 1998, the DDDs of antihypertensive drugs increased of about 79%, the expenditure for these drugs increased of about 115%, while the global pharmaceutical expenditure increased only of 34%. Taking each drug class separately, CCB and ACE-inhibitors are the classes with the higher number of DDDs and the higher expenditure; while alpha-receptor blockers, ACE-inhibitors and AII- antagonists are the classes with the higher cost per DDD. In conclusion this study describes a substantial modification of pharmacoutilization of antihypertensive drugs in Italy along a ten-years span. The agreement between utilization trends and indications of international treatment guidelines, as well as the economic impact on drugs expenditure have been discussed.